Innovation in Structural Analysis and Dynamics for Constructions - Bedon, Chiara; Stochino, Flavio; Stepinac, Mislav (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the construction sector, as in many others, the continuous development of materials, design concepts, and tools for numerical analysis offers new challenges and scenarios to the research and professional communities. For example, the application of building and infrastructure materials and load-bearing components that are particularly sensitive to severe environmental or operational conditions can require specific and even complex methods of analysis, as well as specific performance indicators for their structural verification and assessment. In this regard, especially in recent years, both the building and infrastructure fields have been able to take advantage of increasing technological and productive innovation, which generally takes the form of novel analysis techniques and tools in support of design. This Topical Collection includes original research contributions that are focused on the latest advancements in and development of innovative techniques and solutions for structural analysis, when applied to building and infrastructural constructions. The collection is thus of interest for a multitude of stakeholders, such as academics, structural and construction engineers, architects and other professionals that are involved in the building and infrastructure field.